Brewed Learning : What it is and how does it work? - Nursyuhada’ Ab Wahab,; Melor Md Yunus,; Harwati Hashim, (Multidisciplinary Applied Research and Innovation, 2023)
Today's learners are all digital natives - since they were born in the era of everything at their fingertips. Unfortunately, they lack the direction and guidance to use their handheld devices technology for language learning purposes. Despite the mastery knowledge of IT that they are already equipped with, they still need someone to guide them and assist them in their learning. Therefore, brewed learning concept coined from a case study research is introduced to be practised in an English proficiency course. The course delivered via this concept is tailored purposefully to meet the need of these millennial learners. This concept is designed using the analogy of coffee brewing specifically to suit the 21st-century learning style in which practices were prepared according to the different learning outcomes for tertiary education learners. Besides playing the role of educator, this concept highlights the unique role of a teacher who acts as a barista, brewing the learning activities inside and outside the class. Adopting the blended learning theory by Horn & Staker (2014) as the underlying foundation for the development of this concept, the combination of face-to-face guided activities in the classroom with online activities in Moodle and social media platforms has beautifully shaped the learners’ learning experience in English language and transformed them to be better learners.